Influence of factors and strategies on motivation to learn among middle year students in a private school at the state of Johor - Tan, Hui Yin (2021)
Learning motivation is a crucial indicator to indicate the achievement and performance of a respective student. The past research had shown that students who owned a higher learning motivation would have a higher confidence level, hence results in a better performance in their assessments. However, most of these research backgrounds were based on the students in government school. Among all these studies, only a small amount of them focused on the learning motivation among middle year students in private school. Therefore, this study was aimed to investigate the factors that influence the learning motivation of middle year students in a private school in Johor state and to examine the strategies that will enhance their learning motivation. A case study with in-depth interview was designed to investigate the influence of factors and strategies on the learning motivation among the middle year students. Six students with an age range in between 14 to 16 years old in a private school in Johor state had participated in this study. Generally, they were born with a higher socioeconomic status. The data were processed and analysed by using thematic analysis. The factors that influenced the students’ learning motivation were identified such as family-related factors, school-related factors, social-related factors and personal-related factors. The participants had showed both positive and negative views among these factors except for the personal-related factor. It was the only factor that participants purely showed negative view on it and had been deemed as an obstacle that will affect their learning motivation. Besides, the common strategies implemented by the students were self-regulation, work on a designed study plan, self-alert about the consequences for getting poor grade, goal setting, curiosity and form a study group with peer. Most of the students in this study believed that self-regulation and selfdiscipline were the most effective strategies to enhance their learning motivation. In conclusion, it would be beneficial for the students’ holistic development if the stakeholders in private education system could collaborate with one another to eliminate the hindrance factors that will decline the students’ learning motivation and implement the strategies which promote the students’ motivation to learn.